Implementasi Teori Belajar Humanisme dalam Proses Belajar Mengajar Pendidikan Agama Islam - Aulia Diana Devi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2021)
The process of educating a child must pay attention to the right theory so that children can absorb and receive lessons, and can apply them well. This study aims to describe the learning theory of humanism in learning Islamic religious education. This study uses a qualitative method with a literature study format. The results of this study indicate that the implementation of humanism learning theory in Islamic education is evidenced by several facts, namely, learning conditions, student conditions, and the existence of activities that support the application of the concept of humanism learning. This implementation can also produce active learning, one ofwhich is the discussion and presentation method, which aims to train the independence and courage of students to express their opinions. Community social activities, which aim to train students' socialization and empathy for their environment. Mentoring and coaching, which aims to shape the character and improve the morals of students, reduce juvenile delinquency, and improve student achievement.